THE EFFECTIVENESS OF USING INSTAGRAM ON THE @MEDAN TALK ACCOUNT IN FULFILLING THE INFORMATION NEEDS OF COMMUNICATION STUDIES STUDENTS AT STATE UNIVERSITY OF NORTH SUMATRA STAMBUK 2018 - Meiliana Dwie Tamie; Muhammad Alfikri (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: Social media is a digital platform that facilitates its users to simplify the procces of exchanging information. Instagram is an app that has a gift and is growing throught social media. Researcg in referring to an account and questioning how account is in meeting the information needs of UINSU Communication Science Students. The @MedanTalk account is an account that has actively shared posts related to accidents, natural events, crimes, advertisements and so on specifically in areas around Medan City. Based on the activity of the post, the user of an account with the name @MedanTalk becomes the number one information search acount for the people of Medan City. Keywords: Instagram, Information, Communication